PENERAPAN ASUHAN KEBIDANAN BERKESINAMBUNGAN PADA PEREMPUAN DALAM ASUHAN KEBIDANAN NY. S UMUR 25 TAHUN DI PUSKESMAS TAWANGMANGU KARANGANYAR - Nindi Oktavia; Luluk Fajria Maulida; Angesti Nugraheni (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2025)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are key indicators in assessing maternal and child health as well as the quality of midwifery services. In Tawangmangu District, no cases of maternal mortality were found, but the infant mortality rate was recorded at eight cases. Efforts to reduce MMR and IMR include providing continuous midwifery care (continuity of care). This study aims to implement continuous midwifery care from pregnancy to contraceptive decision-making using a holistic midwifery management approach based on evidence-based practice. This study employs a case study method with Mrs. S, a 25-year-old woman, and her baby as research subjects. Data collection was conducted through primary data, including interviews and direct examinations, secondary data from medical records, and literature studies to support the analysis. Throughout the study, a total of 13 visits were conducted, consisting of three visits during pregnancy, one visit during labor, three visits for newborn care, four visits during the postpartum period, and two visits for contraceptive decision-making. From pregnancy to contraceptive selection, both the mother and baby remained in a normal physiological condition without complications. However, during labor, a pathological condition was observed in the form of retained placenta, where the placenta had not been delivered within 30 minutes after childbirth. To address this issue, manual placenta removal was performed, and uterotonic injection was administered to stimulate uterine contractions. The evaluation of these interventions showed positive results, as the placenta was successfully expelled, bleeding stopped, and uterine contractions proceeded optimally. The findings of this study indicate that continuous midwifery care, from pregnancy to contraceptive decision-making, proceeded normally. Therefore, midwives are expected to continue implementing professional midwifery management at every stage of care. Furthermore, midwives should maintain and enhance their competencies to provide services in accordance with standards, ensuring optimal maternal and infant health.